Effect of heat treatment on the diffusion coefficient of hydrogen absorption in gamma-titanium aluminide - Suardi, Khairmen; Hamzah, E.; Ourdjini, A.; Venkatesh, V. C. (Elsevier, 2007)
Intermetallic alloys based on gamma-titanium aluminide are now regarded as promising candidate materials for high temperature applications such as for aerospace, marine and automotive engine components, due to their high specific strength and modulus. Their oxidation resistance is good, especially at intermediate and high temperature; oxidation resistance can be obtained up to 800 °C. One critical area of application is in combustion engine in aerospace vehicles such as hypersonic airplanes and high-speed civil transport airplanes. This entails the use of hydrogen as a fuel component and it has been widely reported by researchers that these materials exhibit environmental embrittlement in the presence of hydrogen, hence the diffusivity of hydrogen and the effect of hydrogen to the mechanical properties of ?-titanium aluminide is significant and technologically important. A fair amount of research has been carried out to investigate the influence of hydrogen in ?-titanium aluminide. Some researchers reported that a2 and lamellar phases had major influence on the susceptibility of hydrogen to alloys, while hydrogen is too low to penetrate the ?-phases. This research focused on the effect of different microstructures obtained from various heat treatments to the diffusion coefficient and mechanical property after hydrogen absorption. Modification of ?-titanium aluminide can be achieved by heating as-cast binary samples; Ti–45% Al up to 1200 °C (above the Te line) and cooled in three different ways: quenched, air-cooled and furnace-cooled. All samples were then subjected to corrosion attack under cathodically charged with galvanostatic mode for 6 h. The potential variation with time was monitored from these data the values of the diffusion coefficient of hydrogen to -titanium aluminide. D was calculated based on Fick's second law. This result was compared with that obtained from micro-Vickers hardness profiling, which was measured at cross-section area per depth from the top surface corroded. Hydrides formed at the surface were analysed by using image analyser, scanning electron microscopes (SEM) and X-ray diffraction (XRD) equipment. The results showed that different microstructures have an effect on the diffusion coefficient and mechanical property after hydrogen absorption.